Common Genetic Variation Near Melatonin Receptor MTNR1B Contributes to Raised Plasma Glucose and Increased Risk of Type 2 Diabetes Among Indian Asians and European Caucasians - Chambers, John C.; Zhang, Weihua; Zabaneh, Delilah; Sehmi, Joban; Jain, Piyush; McCarthy, Mark I.; Froguel, Philippe; Ruokonen, Aimo; Balding, David; Jarvelin, Marjo-Riitta; Scott, James; Elliott, Paul; et al. (Diabetes (New York, N.Y.), 2009)
Common Genetic Variation Near Melatonin Receptor MTNR1B Contributes to Raised Plasma Glucose and Increased Risk of Type 2 Diabetes Among Indian Asians and European Caucasians John C. Chambers 1 , Weihua Zhang 1 , Delilah Zabaneh 1 , Joban Sehmi 2 , Piyush Jain 2 , Mark I. McCarthy 3 , Philippe Froguel 4 , 5 , Aimo Ruokonen 6 , David Balding 1 , Marjo-Riitta Jarvelin 1 , 7 , James Scott 2 , Paul Elliott 1 and Jaspal S. Kooner 2 1 Department of Epidemiology and Public Health, Imperial College London, London, U.K.; 2 National Heart and Lung Institute, Imperial College London, London, U.K.; 3 Oxford Centre for Diabetes, Endocrinology and Metabolism and Oxford National Institute for Health Research, Biomedical Research Centre, Oxford, U.K.; 4 Section of Genomic Medicine, Imperial College London, London, U.K., and the Centre National de la Recherche Scientifique, 8090-Institute of Biology, Pasteur Institute, Lille, France; 5 UMR 8090-Institute of Biology, Pasteur Institute, Lille, France; 6 Department of Clinical Sciences/Clinical Chemistry, University Hospital Oulu, Oulu, Finland; 7 Institute of Health Sciences and Biocenter Oulu, University of Oulu, Oulu, Finland, and Department of Child and Adolescent Health, National Institute of Health and Welfare, Helsinki, Finland. Corresponding author: Jaspal S. Kooner, j.kooneratimperial.ac.uk . Abstract OBJECTIVE Fasting plasma glucose and risk of type 2 diabetes are higher among Indian Asians than among European and North American Caucasians. Few studies have investigated genetic factors influencing glucose metabolism among Indian Asians. RESEARCH DESIGN AND METHODS We carried out genome-wide association studies for fasting glucose in 5,089 nondiabetic Indian Asians genotyped with the Illumina Hap610 BeadChip and 2,385 Indian Asians (698 with type 2 diabetes) genotyped with the Illumina 300 BeadChip. Results were compared with findings in 4,462 European Caucasians. RESULTS We identified three single nucleotide polymorphisms (SNPs) associated with glucose among Indian Asians at P < 5 × 10 −8 , all near melatonin receptor MTNR1B . The most closely associated was rs2166706 (combined P = 2.1 × 10 −9 ), which is in moderate linkage disequilibrium with rs1387153 ( r 2 = 0.60) and rs10830963 ( r 2 = 0.45), both previously associated with glucose in European Caucasians. Risk allele frequency and effect sizes for rs2166706 were similar among Indian Asians and European Caucasians: frequency 46.2 versus 45.0%, respectively ( P = 0.44); effect 0.05 (95% CI 0.01–0.08) versus 0.05 (0.03–0.07 mmol/l), respectively, higher glucose per allele copy ( P = 0.84). SNP rs2166706 was associated with type 2 diabetes in Indian Asians (odds ratio 1.21 [95% CI 1.06–1.38] per copy of risk allele; P = 0.006). SNPs at the GCK , GCKR , and G6PC2 loci were also associated with glucose among Indian Asians. Risk allele frequencies of rs1260326 ( GCKR ) and rs560887 ( G6PC2 ) were higher among Indian Asians compared with European Caucasians. CONCLUSIONS Common genetic variation near MTNR1B influences blood glucose and risk of type 2 diabetes in Indian Asians. Genetic variation at the MTNR1B , GCK , GCKR , and G6PC2 loci may contribute to abnormal glucose metabolism and related metabolic disturbances among Indian Asians. Footnotes The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked “advertisement” in accordance with 18 U.S.C. Section 1734 solely to indicate this fact. Received December 29, 2008. Accepted July 13, 2009. © 2009 American Diabetes Association